Testing new Centrosema germplasm for acid soils - Schultze-Kraft, Rainer; Keller-Grein, Gerhard (1985)
Adaptation of Centrosema to an acid Ultisol (pH 4.1, 89% Al saturation), was assessed using a collection of 133 accessions representing 12 species, in a preliminary evaluation trial conducted at Santander de Quilichao, Colombia. On the basis of vigour ratings over a period of 21 months, the tested germplasm was classified into 7 cluster groups. All accessions of C. angustifolium, C. pascuorum, C. plumieri, C. sagittatum, C. schottii, C. virginianum and some C. brasilianum and C. pubescens accessions, were poorly adapted to the soil at the site. All accessions of C. macrocarpum, C. arenarium and an undescribed species (Centrosema sp.n.), and several C. brasilianum and C. pubescens accessions, grew well. Rhizoctonia foliar blight mainly affected C. brasilianum. Pseudomonas bacterial blight mainly affected Centrosema sp.n. and C. schiedeanum. In a second experiment, 12 selected accessions of C. macrocarpum, Centrosema sp.n., C. brasilianum, C. pubescens, and C. schiedeanum were compared under cutting over a 24-month period. C. macrocarpum outyielded the other species by 50 100%. Centrosema sp.n. and C. schiedeanum also grew well. Leaf-stem ratio was highest in the non-adapted commercial C. pubescens control and below average in C. macrocarpum and C. brasilianum. The capacity to root on trailing stems was best in C. pubescens, C. schiedeanum and one of the Centrosema sp.n. accessions, and practically non-existent in C. brasilianum. Forage quality of the acid soil-tolerant accessions compared favorably with the commercial control.